Posterior Reversible Encephalopathy in a Patient with Severe Leptospirosis Complicated with Pulmonary Haemorrhage, Myocarditis, and Acute Kidney Injury - W. D. D. Priyankara; E. M. Manoj (Case Reports in Critical Care)
Severe leptospirosis (Weil’s disease) can give rise to multiorgan failure such as acute renal failure, liver dysfunction, coagulopathy, acute respiratory distress syndrome, pulmonary haemorrhage, and myocarditis. Leptospirosis is a biphasic disease characterised by leptospiraemic phase and immunological phase. Although neurological manifestations are rare in leptospirosis, aseptic meningitis, myeloradiculopathy, transverse myelitis, and cerebellar syndrome are well recognised. We report a rare case of posterior reversible encephalopathy syndrome (PRES) in a patient with severe leptospirosis during recovery phase of the illness.